Spatial patterns of forest fires ignition’ causes in mainland Portugal - Meira Castro, Ana C. (2017)
The spatial incidence of Mediterranean forest fire occurrences is inevitably linked to two main factors: the specificity of the environment, which includes the climatic and meteorological conditions of this region as well as the relief and the characteristics of the fuels, and the anthropic use of fire, mainly as a tool to control and modify the use of forest areas. Depending on the social, economic and cultural context of a given region, the causes of the forest fires ignition may spatially differ from country to country and from region to region within the same country. The fire ignition causes significantly influence the fire risk assessment. Thus, both the knowledge and the understanding of the motivations that are at the origin of forest fires are indispensable tools in the design of prevention policies, which must be adapted to the socio-economic, cultural and environmental reality of this country. In this communication, a description of the distribution of the number of forest fires whose causes were investigated, occurred in Portugal between 1996 and 2015, as well the correspondent burned area in this period is made. In addition, it is inspected how the causes of these investigated forest fires are related within the most critical years, as well as in those that were less problematic. The results of this investigation can be used to support an effective planning of fire mitigation and suppression as well an effective implementation of preventive policies of forest fire occurrences.